Mild Synthesis of Symmetric 3,5-Disubstituted Nitrobenzenes - Francisco, Telmo N.; Sousa, Joana L. C.; Guieu, Samuel; Silva, Artur M. S.; Albuquerque, Hélio M. T. (Synlett, 2022)
A mild synthesis of 3,5-disubstituted nitrobenzenes from readily available 3-formylchromones is reported. The developed methodology follows a cascade process, promoted by 1,8-diazabicyclo[5.4.0]undec-7-ene. The proposed mechanism involves an initial Michael addition of nitromethane at C-2 of a 3-formylchromone. The resultant intermediate undergoes another Michael reaction with a second 3-formylchromone molecule. After ring closure through intramolecular cyclization, the aromatization is completed by deformylation, affording the 3,5-disubstituted nitrobenzenes in 52–86% yield. The reported method produces three new C–C bonds in a simple and straightforward manner, and it is consistent with gram-scale synthesis.
Keywords: nitrobenzenes; formylchromones; nitromethane; Michael addition; Nef reaction; cascade reaction